Pentingnya Pendidikan Pancasila untuk Merealisasikan Nilai-Nilai Pancasila dalam Kehidupan Bermasyarakat - Mega Triasya Resmana; Dinie Anggraeni Dewi (STKIP PGRI SITUBONDO, 2021)
The values contained in Pancasila are now starting to fade in society. The number of people who no longer prioritize the values contained in Pancasila makes the writer very sorry for this. So that this article aims so that all of us as members of society can understand more and then be able to apply and always prioritize the values of Pancasila as a guide for living in society. The method used in this research is a qualitative method where the author studies the literature from books, journals, e-books, and articles. And the results obtained show that there are many ways we can realize or apply the values of Pancasila in social life. Pancasila has functions and values that we must know and then understand and also apply in this life. For this reason, as good citizens we must be able to review and apply and make guidelines for the values of Pancasila so that we can live in a good society and in accordance with existing norms and rules.